Dengue: A Practical Experience of Medical Professionals in Hospital - Islam, Quazi Tarikul; Basher, Ariful; Amin, Robed (Journal of Medicine, 2012)
Background: Dengue remains endemic and frequently intensifies into epidemics in Bangladesh since 2000 resulting in frequent hospitalizations. Materials & Methods: A prospective observational study was carried out to determine the clinical parameters of the subjects for hospitalization and the pattern of presentation of dengue fever in hospital care from July, 2010 to December, 2010. Result: Total 50 cases were selected consecutively and diagnosed clinically as dengue, and were classified into 3 groups, i.e. 25 cases of classical dengue fever, 3 cases of dengue fever with unusual haemorrhage, 22 cases Dengue haemorrhagic fever (DHF-I and DHF-II) and all were discharged uneventfully. Among them 33(66%) were male and outnumbered 17(34%) were female. Mean ages of the subjects were 30.91 ±10.314, 34.33 ± 16.29 and 33.91 ± 14.72 years in respective groups. Majority had profound weakness, headache, myalgia, anorexia, nausea, and vomiting and itching. Diarrhoea, abdominal pain, organomegaly, ascites, and pleural effusion were not infrequent complaints of Dengue haemorrhagic fever patients, whereas occasional complaints in other groups. There is a linear relationship between platelet count and SGPT (p-0.037). Hametocrit value also markely increased in dengue haemorrhagic fever (m- 42.5) but not in dengue fever with unusual haemorrhage (m-31). Biochemical marker specially Hct may be a good predictor to differentiate different presentation of dengue fever. Conclusion: Patients with dengue syndrome showed varied presentation and the symptoms were nonspecific. So much attention has to be paid for early diagnosis and management. DOI: http://dx.doi.org/10.3329/jom.v13i2.12751 J Medicine 2012; 13 : 160-164